The role of platelet-rich plasma in biomedicine: A comprehensive overview - Zhixin Zhang; Peng Liu; Xinmiao Xue; Zhiyu Zhang; Li Wang; Yvke Jiang; Chi Zhang; Hanwen Zhou; Shuhan Lv; Weidong Shen; Shiming Yang; Fangyuan Wang (iScience)
Summary: Biomedicine has seen significant advancements in the 21st century, with platelet-rich plasma (PRP) playing a crucial role in clinical practice. This blood derivative, enriched with platelet components, has shown great potential for promoting tissue repair and regeneration. Its wide range of applications and the presence of anti-inflammatory and growth-promoting factors make it a valuable tool in the field of biomedicine. The exploration of PRP in clinical settings has been gaining momentum. Despite its cost-effectiveness, safety, and therapeutic efficacy, the widespread clinical adoption of PRP has been hindered by the absence of consistent preparation standards and standardized treatment protocols. This article provides a comprehensive analysis of the clinical uses, physiological roles, molecular mechanisms, and preparation techniques of PRP in biomedicine. The aim is to offer a thorough understanding of the potential applications and benefits of PRP in medical practice.